Antibacterial and antifungal activity of derivatives 3-(alkylthio)-4-R-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazole - O. A. Suhak; O. І. Panasenko; Ye. G. Knysh; O. M. Kamyshny (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The amount of antibiotics has increased over the past decade. This also resulted in increase of microorganisms’ resistance to this class of drugs. Therefore, the synthesis of new compounds that have exhibited antimicrobial and antifungal activity and low level of side effects is an important issue of modern pharmacy. The 1,2,4-triazole system is very promising in this aspect.